Developing physical health, fitness and well-being through gymnastics (7-11) : a session-by-session approach - Carroll, Maggie; Hannay, Jackie (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2012)
This practical and easy-to-use teacher's guide is the brand new edition of the popular workbook Gymnastics 7-11. It takes a session-by-session approach to teaching physical development and well-being through gymnastics for the 7-11 age range.
Keywords: Gymnastics for children; Movement education